Evaluation of silver nanocomposite polymer inclusion membranes (PIMs) for trace metal transports: Selectivity and stability studies. (October 2020) - Maiphetlho, Kgomotso; Shumbula, Ndivhuwo; Motsoane, Nthabiseng; Chimuka, Luke; Richards, Heidi
Abstract: The presence of trace metals in polluted mine water remains a concern due to its adverse effects on human health. This paper evaluates a PVC-D2EHPA based PIM containing silver nanoparticles as a tool to extract and measure trace metals in polluted water. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), contact angle and water uptake measurements were used to characterise the PIMs. The contact angle measurements highlighted that the presence of AgNPs modified the membrane's hydrophobic/hydrophilic character. The affinity of a PIM containing (40 w.t% D2EHPA, 10 w.t% AgNPs and 50 w.t% PVC) towards a range of divalent cations (Co 2+, Ni 2+, Cu 2+, and Cd 2+ ) in synthetic water solutions, based on the percentage recovery factor of the extracted metal ions, was found to follow the order; Cd 2+ (94) > Cu 2+ (87) > Ni 2+ (78) > Co 2+ (67). This order can be explained by the corresponding hydration energies of the metal cations. The stability of the PIM was compromised during repeated cycle operations despite an improvement of hydrophilicity with introduction of AgNPs. This was indicated by an appreciable leaching of the carrier (D2EHPA) and AgNPs in a 4:1 ratio. The silver nanocomposite PIM was tested in dam water, where no matrix effect was observed on metal ion transport efficiency. The obtained transport % efficiencies for the metal ions were Cd 2+ (88), Cu 2+ (80), Ni 2+ (62), Co 2+ (70) and Fe 2+ (37) respectively. The newly synthesized PIM is a promising tool for transport of the target metals from water systems, however further studies are needed to improve the stability of both the carrier and nanoparticles in the membrane.